Persoalan Status Sebagai Anak-anak Abraham dalam Surat Galatia - Samuel Benyamin Hakh (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract In the apostle Paul's letter to the Galatians, one of the principal theological debate sticking to the surface is the status as children of Abraham through circumcision. Because according to a group of Jews Christian who came to Galatia, Gentile Christians shall be circumcised, and implement the law, if they want to obtain salvation. Because safety is only given to those who become the children of Abraham in full. On the other hand, Paul rejected that obligation. According to Paul, by faith in Christ, the son of Abraham, Christians in Galatia, having status as the children of Abraham and inherit the blessings of God's promise that is salvation. In this article I argue that the debate was due on the one hand, Jewish Christian groups that cling to the tradition of circumcision because of the tradition that has been in effect since Abraham and believed to be the way of salvation, while Paul emphasis on faith and obey the decision of the council in Jerusalem that circumcision is not required for the non-Jewish. Abstrak Dalam surat Rasul Paulus kepada jemaat di Galatia, salah satu pokok perdebatan teologis sosiologis yang mencuat ke permukaan adalah status sebagai anak-anak Abraham melalui sunat. Sebab menurut kelompok orang Kristen Yahudi yang datang ke Galatia, orang Kristen non-Yahudi wajib disunat dan melaksanakan hukum Taurat, jika mereka ingin beroleh selamat. Sebab keselamatan hanya diberikan kepada orang-orang yang menjadi anak-anak Abraham secara penuh. Di pihak lain, Paulus menolak kewajiban itu. Menurut Paulus, oleh iman di dalam Kristus, anak Abraham itu, orang Kristen di Galatia telah beroleh status sebagai anak-anak Abraham dan mewarisi janji berkat Allah itu, yakni keselamatan. Dalam artikel ini saya berargumentasi bahwa perdebatan itu terjadi karena pada satu pihak, kelompok Yahudi itu berpegang teguh kepada tradisi sunat karena tradisi itu telah diberlakukan sejak Abraham dan diyakini sebagai jalan keselamatan, sementara Paulus menekankan pada iman serta taat kepada keputusan sidang di Yerusalem bahwa sunat tidak diwajibkan bagi orang non-Yahudi.